Associations between simultaneous alcohol and cannabis use and next-day negative affect among young adults: The role of sex and trait anxiety. (December 2021) - Linden-Carmichael, Ashley N.; Hochgraf, Anna K.; Cloutier, Renee M.; Stull, Samuel W.; Lanza, Stephanie T.
Highlights: Negative affect was higher on no substance use days relative to alcohol-only, cannabis-only, or SAM use days. SAM use was associated with higher next-day negative affect for female participants with higher anxiety. Anxiety and sex are critical factors in the link between SAM use and affect. Abstract: Background and aims: The simultaneous use of alcohol and cannabis ("simultaneous alcohol and marijuana [SAM] use") is common among young adults and associated with negative substance-related consequences. SAM use may be tied to fluctuating mood states such as negative affect and individual characteristics including trait level of anxiety and sex. However, little is understood about their collective role. In this study, we sought to understand the daily link between SAM use and negative affect and whether this link might differ by both trait anxiety and sex. Method: Participants were 154 young adults (57.8% female, 72.7% White, M age = 20.2) who completed baseline surveys on trait anxiety symptoms and up to 14 consecutive daily surveys on their substance use and affective states. Results: Multilevel models tested for associations of type of substance use day (i.e., alcohol-only days, cannabis-only days, and no use days relative to SAM use days) with next-day negative affect. Three-way and lower order interactions were tested for substance use day type, anxiety, and sex. Two three-way interactions between cannabis-only days, anxiety, and sex and between alcohol-only days, anxiety, and sex emerged such that SAM use was associated with greater next-day negative affect relative to single substance use days particularly among female participants with elevated anxiety. Conclusions: Anxiety and sex are salient factors in the link between SAM use relative to single-substance use and daily negative affect. Study findings reinforce the need to account for all of these factors in order to develop maximally efficacious substance use interventions.